Mere music or more? Investigating the effects of soundtracks in video game narratives - Callendar, Chaz, author; Humphrey, Michael, advisor; Martey, Rosa, committee member; Parks, Elizabeth, committee member (Colorado State University. Libraries, 2021)
Narratives in video games can be highly complex, and due to Game Studies' over-reliance on Film scholarship, the complexities of the co-creation of these narratives have yet to be understood. There are many elements within games that are not present within film, and this can alter how a narrative is experienced within the medium as compared to film (Salen & Zimmerman, 2004). One of the major elements of narratives that is understudied within games is music. This thesis analyzed player reports of how music affected their ability to experience the narrative within two games. Specifically, how the music affected their transportation into the world, as well as how the music affected their ability to identify with the main characters. Through a combination of in-game and postgame interviews, transcripts were created and thematically analyzed along with the video and audio data. Through this analysis, participants consistently demonstrated that they were unable to identify or recognize the music with the game. However, the emotions evoked from the music seemed to be the same emotions felt during the scenes where those tracks existed. While the explicit memory of the music was almost nonexistent, there was evidence of implicit memory of this music embedded within the world and characters of the game. Finally, rather than attributing music as the source of the emotions used by the narrative, it is possible that the music was simply part of the narrative, so any reference to the music alone was inaccessible to the players.
Keywords: music; transportation; identification; video games; narrative